3(x-7)-2(x+11)=21

Simple and best practice solution for 3(x-7)-2(x+11)=21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-7)-2(x+11)=21 equation:


Simplifying
3(x + -7) + -2(x + 11) = 21

Reorder the terms:
3(-7 + x) + -2(x + 11) = 21
(-7 * 3 + x * 3) + -2(x + 11) = 21
(-21 + 3x) + -2(x + 11) = 21

Reorder the terms:
-21 + 3x + -2(11 + x) = 21
-21 + 3x + (11 * -2 + x * -2) = 21
-21 + 3x + (-22 + -2x) = 21

Reorder the terms:
-21 + -22 + 3x + -2x = 21

Combine like terms: -21 + -22 = -43
-43 + 3x + -2x = 21

Combine like terms: 3x + -2x = 1x
-43 + 1x = 21

Solving
-43 + 1x = 21

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '43' to each side of the equation.
-43 + 43 + 1x = 21 + 43

Combine like terms: -43 + 43 = 0
0 + 1x = 21 + 43
1x = 21 + 43

Combine like terms: 21 + 43 = 64
1x = 64

Divide each side by '1'.
x = 64

Simplifying
x = 64

See similar equations:

| 7-(11-2x)=6 | | 7x+6y= | | 2(3x+6)-4(x-2)=24 | | 10-2x=19-4x | | 5x+9+7x=0 | | -4(3-p)=5(p+1) | | 5c-4=8c+2 | | 23z-13z=50 | | 5p+2p=28 | | 12m-3m=18 | | 4y+7y=22 | | 16x-4x=36 | | 3a+5a=16 | | y+8=3x | | 19=10-b | | 3c-4=5 | | 4n+8=12 | | -12n-19=77 | | 3f=17 | | 6x-4(x-6)=-10 | | 15+7x=45 | | -31=8-6p-7p | | -30+-42= | | -30-42= | | 145=10x-8x | | 8x+11=8x+8 | | 7x+3=7x+3 | | 8x-2(x-8)=-14 | | 11x+25=7x+15 | | 4x+5=4x-1 | | 13=-2+3w | | 4x-9(x-1)=20-5x |

Equations solver categories